Educational Game Tool Flash Card Hijaiyyah Letter as A Medium of Stimulation of The Development of Moral and Religious Values of Children In TK Al Gazali Desa Metere Lakudo Subdistrict - Risman, Kadar; Saleh, Rachman; Selvi, Selvi (Lembaga Riset dan Inovasi Masyarakat Madani, 2022)
The community service project that we conducted on October 30, 2021 at TK Al Gazali Desa Metere District Lakudo Central Buton District aims to provide teachers with insight into effective media for learning in Early Childhood, to improve teacher skills in creating educational game tools, and to provide teachers with insights and equip them to develop learning media in the form of Educational Game Tools for Children in their Early Age. Teachers at Al Gazali Kindergarten in Metere Village, Lakudo District, Central Buton Regency were the intended recipients of this activity. The topic of dedication concerns the instructors' degree of awareness and ability, as well as the limitations of educational gaming instruments that can help pupils at Al Gazali Kindergarten in Metere Village acquire moral and religious values. Three phases are necessary to resolve the problem: preparation, implementation, and assessment. The planning stage begins with observations to ascertain the state of educational gaming instruments in use at the school. The implementation stage is comprised of training in the creation of Hijaiyyah Letter Flash Cards, beginning with the delivery of material in the form of perentase via lecture methods, followed by Q&A or discussion and training in the form of a workshop in the creation of APE Flash Cards Hijaiyyah Letter as a means of improving teacher skills. Monitoring and assessment concludes the process. Monitoring and evaluation are accomplished by the collection and analysis of data at each level. The training results indicated a degree of success, with kindergarten teachers Al Gazali Desa Metere gaining a better understanding of the importance of APE in stimulating the development of moral and religious values, teachers improving their skills in creating APE Flash Cards to aid in the learning process, teachers responding positively to the training conducted, and teachers successfully completing the creation of APE Flash Card Hijaiyyah, according to the number.